Access Spacing Based on Turning-Vehicle Acceleration. Issue 1 (2017) - Gattis, James L.; Chimka, Justin R.; Evans, Andrew
Spacing between access connections—whether between a public roadway and a driveway or between two successive driveways—is one of the core techniques employed to effect access management. Several rationales reflecting different types of traffic interactions have been developed as a basis for minimum spacing distances. A small study was done in which two attributes were recorded: positions of vehicles turning from a side street and accelerating along the through roadway and time required for vehicles to turn left from the through roadway into a driveway. The vehicle movement described—a vehicle turning right from the side street into the through roadway—may be more likely to surprise the driver contemplating a left turn from the through roadway. Information derived from these observations, combined with perception–reaction values found in the literature, offers a basis for minimum spacing criteria that addresses one of many types of traffic interactions related to spacing, where a left turn is allowed across the through roadway downstream of another connection. These findings provide one more means to assess spacing along four-lane arterials in a developed suburban environment. A study with a greater scope to expand these findings is also proposed.